In vitro effects of doxycycline on inflammatory cytokines and gelatinases in chronic rhinosinusitis - Sommer, Ulrich; Schultz, Johannes D.; Großbaier, Judith; Stern-Sträter, Jens; Hörmann, Karl; Sauter, Alexander (In vivo, 2012)
Background/Aim: The pathophysiology of chronic rhinosinusitis (CRS) is unknown, but the majority of patients suffer from eosinophilic infiltration. We hypothesised that doxycycline might alter the eosinophil-associated expression of interleukin-5 (IL-5) and eotaxin-3 in CRS and also the expression of matrix metalloproteinase 9 (MMP-9), being involved in the tissue-remodelling in CRS. Materials and Methods: After obtaining samples from 10 CRS patients with and without nasal-polyposis undergoing functional endoscopic sinus surgery and two healthy individuals, the expression of IL-5, eotaxin-3 and MMP-9 were evaluated by an ELISA technique. The tested agent was doxycycline at 0.1 or 1 mg/ml. Results: IL-5 levels remained unchanged, but eotaxin-3 levels actually increased under doxycycline treatment. The only marker showing a slight drop was MMP-9, albeit not significant. Conclusion: As first clinical trials with doxycycline in the treatment of CRS produced reasonable results we could demonstrate that the underlying pathology is more complex, and doxycycline affects only a part of the factors believed to support the chronic infection of the respiratory mucosa.
Gesehen am 30.07.2018